Introduction to land and animal ownership - Benson, Delwin E., speaker; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Private lands are used for wildlife and livelihoods on 2/3rds of the US including Colorado. Eastern US and Colorado is more private and the West more public. In Colorado, private lands dominate the eastern short grass prairies, western sagebrush steppes, hills, and mountain valleys. High elevation alpine, forests and range lands are often public, managed by government agencies. National, state, county, and city parks, wildlife areas, and two of 36 sections in townships, called state land trust lands are intermixed with private lands fragmenting ownership, uses, and management. In Colorado, wildlife has seasonal movements north and south, up and down elevations, and to and from private and public lands. Wildlife tends to be on private lands for transitional uses and wintering while on public lands during summers based on food and shelter needs, with exceptions. Hunters come to the West to hunt with open access on abundant and no cost public lands, but prefer private lands when access is granted and if the costs are within budgets. Public lands can become overused in space, time and resources. Access to private lands is appealing to users because animal numbers and recreational experiences can be of higher quality with more private control. Charging access fees is increasing on private lands. Wildlife in the US belongs to the people in custodial jurisdiction of state wildlife agencies with federal responsibilities for migratory and endangered species, and all wildlife while on their lands. Those with wildlife on their lands can have positive or negative influences.

Why should landowners conserve wildlife rather than eat it, frighten it, kill it out of anger, or poach it for illegal markets? What incentives promote nature conservation and biodiversity on private and communal lands? The needs, roles, responsibilities, and spirit of private and communal sectors increase to take action for nature conservation on their lands as public lands and opportunities decrease. It is progressively difficult to protect land resources by central governments as human population pressures increase. Likewise, nature conservation must compete with other land uses. Private and communal land managers must adapt to land use changes, climate variables, markets, and dilemmas of rejecting wildlife, coping with wildlife, or encouraging wildlife and nature conservation positively. People want wildlife unless it affects them negatively; consequently, we must work with other professionals, private landowners and outdoor users to find the spirit, empowerment, support, and logistics to have people and wildlife on the landscape without evicting the other. 'We will conserve only what we love, we will love only what we understand, and we will understand only what we are taught' according to Baba Dioum born in Senegal in 1937. Aldo Leopold (1949) said that conservation is a state of harmony between man and land and despite nearly a century of propaganda, conservation still proceeds at a snail's pace. 'On the back forty we still slip two steps backward for each forward stride.' How do we have wildlife and livelihoods on lands without evicting the other?

Connect people to conservation locally by accessing existing programs and improving access to private lands. During my near 50 year career, agencies and organizations have funded and conducted environmental outreach and private access programs using trained staff and volunteers. Unfortunately, outcomes have not solved the urbanizing dilemma of a society disconnected from the land. Recruitment and retention programs for wildlife interests have not replaced those who exited. The business of doing conservation suffers when fewer participants pay fees, buy equipment, and spend money on rural tourism. Lacking are integrated networks of programs, communications, leaders, mentors, and motivations to be in nature when modern and urbanized life provides competitive options such as electronic gadgets and urban forms of recreation. Contacts with rural landowners are lost. Landowners, agencies, nongovernmental organizations, universities, parents, and friends have a greater leadership responsibility to encourage interest in outdoor behaviors and access to private lands that lead to sound nature conservation and personal stewardship. We need to teach conservation frequently nearest to home, populate regional programs through joint planning and communications, and create new approaches to access private lands for the benefits of producers and users. Users in the United States generally do not feel comfortable or are unsuccessful to gain access. Some users do not want to pay for the privileges that landowners provide. Some landowners do not want the bother of wildlife or recreationists. Use of private lands would likely be higher if access was easier to negotiate. The lure of interesting places, history, stories, and wildlife opportunities makes private lands prime locations to teach and learn about conservation.
Private and communal wildlife and livelihoods: the future of conservation
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Presented during Plenary Session III.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses